Changes in kidney fat upon dietary-induced weight loss - Spurny, Manuela; Jiang, Yixin; Sowah, Solomon A.; Nonnenmacher, Tobias; Schübel, Ruth; Kirsten, Romy; Johnson, Theron S.; Stackelberg, Oyunbileg von; Ulrich, Cornelia; Kaaks, Rudolf; Kauczor, Hans-Ulrich; Kühn, Tilman; et al. (Nutrients, 2022)
As the metabolic role of kidney fat remains unclear, we investigated the effects of dietary weight loss on kidney fat content (KFC) and its connection to kidney function and metabolism. Overweight or obese participants (n = 137) of a dietary intervention trial were classified into quartiles of weight loss in a post hoc manner. Kidney sinus (KSF) and cortex fat (KCF) were measured by magnetic resonance imaging at baseline, week 12 and week 50. Weight loss effects on KFC were evaluated by linear mixed models. Repeated measures correlations between KFC, other body fat measures and metabolic biomarkers were obtained. KSF, but not KCF, decreased significantly across weight loss quartiles at week 12 (quartile 4: −21.3%; p = 0.02) and 50 (−22.0%, p = 0.001), which remained significant after adjusting for VAT. There were smaller improvements regarding creatinine (−2.5%, p = 0.02) at week 12, but not week 50. KSF, but not KCF, correlated with visceral (rrm = 0.38) and subcutaneous fat volumes (rrm = 0.31) and liver fat content (rrm = 0.32), as well as diastolic blood pressure and biomarkers of lipid, glucose and liver metabolism. Dietary weight loss is associated with decreases in KSF, but not KCF, which suggests that KSF may be the metabolically relevant ectopic fat depot of the kidney. KSF may be targeted for obesity-related disease prevention.